Economic labor arbitration as a conflicts resolution mechanism in Peru - Girao La Rosa, Juan Carlos (2017)
The amount of labor law arbitrations has significantly increased through the last years. This has concurred with a legal modification that establishes specific causes for facultative arbitration.In this paper, the author analyzes this normative change while clarifying the polemics over its juridical nature and inquiring about its future effects regarding labor relationships disputes resolution.